NF‐κB, CRE and YY1 elements are key functional regulators of CMV promoter‐driven transient gene expression in CHO cells. Issue 7 (23rd February 2015) - Brown, Adam J.; Sweeney, Bernie; Mainwaring, David O.; James, David C.
Abstract Transient gene expression (TGE) in CHO cells is utilized to produce material for use in early stage drug development. These systems typically utilize the cytomegalovirus (CMV) promoter to drive recombinant gene transcription. In this study, we have mechanistically dissected CMV‐mediated TGE in CHO cells in order to identify the key regulators of this process. An in silico analysis of the promoter composition of transcription factor regulatory elements (TFREs) and the CHO cell repertoire of transcription factors identified eight TFREs as likely effectors of CMV activity. We determined the regulatory function of these elements by preventing their cognate transcription factors from binding at the CMV promoter. This was achieved by both scrambling promoter binding site sequences and using decoy molecules to sequester intracellular transcription factors. We determined that the vast majority of CMV activity is mediated by just two discrete TFREs, showing that simultaneous inhibition of NF‐κB and CRE‐mediated transactivation reduced CMV‐driven transient secreted alkaline phosphatase (SEAP) production by over 75%. Further, we identified a mechanism by which CMV‐mediated TGE is negatively regulated in CHO cells, showing that inhibition of YY1‐mediated transrepression increased SEAP production 1.5‐fold. This work enables optimization and control of CMV‐mediated TGE in CHO cells, in order to improve transient protein production yields.